Venous bypass grafts versus arteriovenous loops as recipient vessels for microvascular anastomosis in lower extremity reconstructions: a matched-pair analysis - Henn, Dominic; Bigdeli, Amir Khosrow; Horsch, Miriam; Weiß, Christel; Kühner, Clemens; Hirche, Christoph; Schmidt, Volker-Jürgen; Kneser, Ulrich (Microsurgery, 2020)
Background Limb salvage in patients with peripheral vascular disease (PVD) and soft tissue defects often requires both a restoration of blood flow to the lower extremity and soft tissue coverage. Outcomes of free tissue transfer may be affected by vein grafts, which can be used for the placement of an autologous venous bypass or an arteriovenous (AV) loop leading to different hemodynamic situations. The purpose of this study was to investigate whether free flap anastomosis to a bypass or an AV loop can be performed with comparable results. Methods We performed a matched-pair analysis of 22 patients with PVD undergoing free flap reconstructions of the lower extremity with end-to-side anastomosis to an autologous venous bypass (n = 11, 1 female and 10 male patients) or an AV loop (n = 11, 2 female and 9 male patients). Defects caused by trauma, infection, ulcer, or fasciotomy were reconstructed in each group with 5 muscle-based flaps, 3 parascapular flaps, 2 anterolateral thigh (ALT) flaps, and 1 conjoined latissimus dorsi and parascapular flap. Postoperative complications including thromboses, flap failures, wound complications, and hematomas were compared. Results Postoperative complication rates including 1 venous pedicle thrombosis (9%vs. 0%, P = 1.0), minor (18% vs. 9%, P = 1.0) and major wound complications (45% vs. 27%, P = .69) as well as hematomas (27% vs. 36%, P = 1.0) did not show relevant differences between the groups. Flap failures were absent in both groups. Conclusion In patients with PVD, autologous venous bypass grafts may be used for end-to-side anastomoses of free flaps, with postoperative outcomes being comparable to AV loop reconstructions.
First published: 24 January 2019
Gesehen am 30.01.2020